The Potential of Walnut Seeds (Canarium indicum L.) in Repairing The Genotoxicity Effect of Mercury on Mice Erythrocytes - Cakra Haryo Wibowo; Essy Oktarina; Rafika Destiana Wardani; Khoirul Ngibad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Hydrargyrum (familiar as mercury) is a persistent transition metal element. They are known as bio-accumulative properties that are dangerous to the environment and has serious damaging effects on biota, including genetic changes or mutagenesis. Moreover, it can accumulate indirectly in the human body due to the consumption of products that have contaminated. Whereas, ellagic acid has reported as one of 13 flavonoid compounds that have potential as an anti-mutagen and anti-cancer in the walnuts seeds. This study was aimed to ensure the potential extent of ellagic acid extracts in walnut seeds to reducing and repairing the genotoxicity effects of mercury. Therefore, using the experimental method, this study was divided into several test treatments. Two controls treatment as a comparison of the presence of micronucleus with group tests that given a 20 ppm mercury dosage. Then continued with the addition of walnut seed extract with various dosage (10, 15, and 20 ppm) by oral injection continuously for two weeks as a recovery process to reducing and repairing the genotoxicity effect of mercury. The significant results showed that there are differences between pre and post-treatment. It indicated that the extract has the potential for improving and reducing the genotoxicity effect of mercury. The data were evaluated and obtained the total micronucleus from the smear of peripheral blood of mice by comparing the total micronucleus before and after giving of walnut extract.